Acessibilidade e resolutividade em assistência oftalmológica para o SUS - Satto, Larissa Horikawa [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Objective: the main goal is to determine if a mobile eye clinic can be used to improve access to eye care. Furthermore is shown the individual profiles that need ophthalmic examination, the main ocular diseases and the treatments necessary to solve the problems. Methods: a cross sectional survey was conduct in fourteen cities of middle-west region of São Paulo St/Brazil, in localities which requested the service provided by the mobile ophthalmic unit. The sample was intentional, the participants were of Brazilian Unified Health System users, who spontaneously search for eye care. Both men and women were eligible, without restrictions about age or socioeconomical status. The data were transferred to Excel Table and statistical analysis was performed. Results: A total of 6878 people participated in this study, 65.54% were female. The mean age was 44 years old (range 4 months to 96 years). The most common ocular complaints were near visual difficulty (60.35%), followed by visual difficulty for distance (55.99%) and headache (26.69%). The main diagnosis was refractive errors (78.60%), followed by cataract (9.60%) and pterygium (8.31%). Spectacles was prescribed to 60% and was maintained to 10%, and for about 28%, only orientation was necessary. 18.10% of the sample were referred to the Ophthalmology Service of Botucatu Medical School, highlighting the cases of oculoplastic surgery (36.14%) and cataract (31.80%). The prevalence of low vision and blindness and the prescribed treatment were similar in both cities with or without ophthalmologist, the need for referral to a tertiary center was highter for patients who live in cities with ophthalmologist. Conclusion: the most common problem for patients from the Brazilian Unified Health System who sought for eye care was the need of spectacles prescription. Mobile eye clinic has a high degree of resoluteness for eye problems, with a small percentage in need to referrals to tertiary service, ...

Objetivo: o objetivo principal deste estudo foi verificar se unidades móveis podem ser consideradas resolutivas para melhorar o acesso a consulta oftalmológica e promover a saúde ocular. Outros objetivos foram definir o perfil dos indivíduos que necessitavam do exame oftalmológico, as principais afecções encontradas e as condutas necessárias para resolução do problema detectado. Material e métodos: estudo prospectivo, transversal, de amostra de conveniência, visando atendimento oftalmológico para as afecções de baixo nível de complexidade, realizado em municípios do centro-oeste paulista que solicitaram o atendimento realizado por uma unidade móvel oftalmológica. Foram considerados elegíveis indivíduos de ambos os sexos, sem restrição quanto a idade ou condição socioeconômica. Os dados dos atendimentos foram transferidos para Tabela Excel e analisados usando o teste t de Student e qui-quadrado. Resultados: foram atendidos 6.878 indivíduos, em 14 municípios. Pertenciam ao sexo feminino 65,54%, com idade de 4 meses a 96 anos (média=44 anos). As queixas oculares mais frequentes foram dificuldade visual para perto (60,35%), dificuldade visual para longe (55,99%) e cefaléia (26,69%). As ametropias foram a razão da procura pelo atendimento para 78,60%, seguidas pela catarata (9,60%) e pterígio (7,02%). Para cerca de 60% dos indivíduos, foi prescrito correção óptica, para 10% foi mantida a correção óptica em uso e para 28% foi necessário apenas orientações. Tiveram alta após exame 81,70% dos indivíduos e 18,10% foram encaminhados para o serviço terciário, destacando-se os casos direcionamentos para os ambulórios de plástica ocular (36,14%) e catarata (31,80%). A prevalência de deficiência visual e o tratamento prescrito foram semelhantes em municípios que dispõem ou não de oftalmologista na localidade; a necessidade de encaminhamento ao serviço terciário foi maior para os municípios com...
Keywords: Olhos - Doenças; Tratamento oftalmologico; Sistema Único de Saúde (Brasil); Acesso aos serviços de saúde; Eye - Diseases and defects